Critical Appraisal of the Curricula of MD Anesthesiology Programs in Nepal using Harden’s 10 Questions - Paneru, Hem Raj; Joshi, Pankaj; Lamsal, Ritesh (Journal of Institute of Medicine Nepal, 2025)
Introduction Anesthesiology in Nepal is evolving beyond its traditional operating room role, increasingly encompassing critical care, pain management, and multidisciplinary support. As surgical and procedural services expand, there is a growing demand for anesthesiologists with advanced clinical, leadership, and research skills. Ensuring that MD Anesthesiology curricula are robust and contextually relevant is essential for meeting Nepal’s diverse healthcare needs. This study aimed to assess whether the curricula included the key principles as outlined in Harden’s 10-question framework. Methods This study critically evaluated the MD Anesthesiology curricula from major Nepalese institutions using Harden’s Ten Questions framework. Curricular documents were collected and analyzed independently by multiple reviewers. Results All programs follow a three-year structure with a mandatory thesis, but variability exists in curricular detail, organization, and emphasis on research or community-based components. Needs assessments and stakeholder engagement are generally absent. Educational objectives are broad but often lack focus on leadership and interprofessional skills. Teaching and assessment methods remain largely traditional, with limited use of active learning or competency-based approaches. Communication of curriculum details and educational environment standards also vary widely. Conclusion MD Anesthesiology curricula in Nepal require comprehensive reform. Implementing evidence-based needs assessments, modern educational strategies, and continuous quality improvement will better prepare graduates to meet the complex challenges of contemporary healthcare.